2006
DOI: 10.1016/j.polymer.2005.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Order and segmental mobility during polymer crystallization: Poly(butylene isophthalate)

Abstract: The influence of the development of crystalline structure on the segmental dynamics of the amorphous phase in poly(butylene isophthalate) (PBI) has been studied by a combination of relaxation and scattering techniques. By means of dielectric spectroscopy (DS) the dynamics of both amorphous and semicrystalline PBI samples has been observed in a wide frequency and temperature range. The evolution of the crystalline phase with time has been studied in a range of temperatures, starting from initially glassy PBI by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 38 publications
6
55
1
Order By: Relevance
“…Several studies have already presented the dielectric properties of POSS/ polymer nanocomposites using dielectric spectroscopy (DS) [52][53][54]. Dielectric spectroscopy (DS) can be very sensitive method for analyzing the effect of polymer crystallization [55]. Therefore, for the neat PTT-PTMO and PTT-PTMO/1.0POSS nanocomposites, the DS measurement has been performed.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…Several studies have already presented the dielectric properties of POSS/ polymer nanocomposites using dielectric spectroscopy (DS) [52][53][54]. Dielectric spectroscopy (DS) can be very sensitive method for analyzing the effect of polymer crystallization [55]. Therefore, for the neat PTT-PTMO and PTT-PTMO/1.0POSS nanocomposites, the DS measurement has been performed.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…Another possibility for explaining this correlation peak could be the presence of crystallites inside the matrix [47][48][49][50][51], but the XRD plot for this membrane did not show any evidence for crystallinity at room temperature [43]. This fact suggested that the membrane M2 was composed by richer-PPSQ/SiO 2 and PDMS/SiO 2 phases.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 89%
“…This crosslinking comes from the hydrogen bonds that formed between the oxygen of PEG and the α-hydrogen of the chlorine groups of CPVC structure. Therefore, α'-process for CPVC-PEG blend can be attributed to the rigid amorphous phases that located between adjacent lamella inside the lamellar stacks of CPVC [25,26].…”
Section: Miscibility Study Based On Tg Analysismentioning
confidence: 99%